Aortic Valve Repair Versus Replacement for Aortic Regurgitation: Effects on Left Ventricular Remodeling. Issue 1 (17th October 2014) - Regeer, Madelien V.; Versteegh, Michel I.M.; Klautz, Robert J.M.; Stijnen, Theo; Schalij, Martin J.; Bax, Jeroen J.; Ajmone Marsan, Nina; Delgado, Victoria
Abstract Background Left ventricular (LV) reverse remodeling after aortic valve replacement (AVR) for aortic regurgitation (AR) is associated with superior prognosis. The outcomes of valve‐sparing aortic root replacement techniques on LV performance have not been compared with LV reverse remodeling in AVR. The present evaluation compared the extent of long‐term LV reverse remodeling in patients with aortic root pathology and/or AR who underwent aortic valve repair (AVr) with patients who underwent AVR. Methods A total of 226 patients (54.7 ± 14.3 years, 63% male) with AR or aortic root pathology who underwent AVr (n = 135) or AVR with the Freestyle® stentless aortic root bioprosthesis [Medtronic, Inc.; Minneapolis, Minnesota] (n = 91) were included in the present retrospective evaluation. LV volumes and ejection fraction were assessed preoperatively, postoperatively (before hospital discharge) and during follow‐up. Results Baseline characteristics were comparable between patient groups, except for higher prevalence of bicuspid aortic valve anatomy among AVR patients (38% vs. 16%, p < 0.001). In addition, patients undergoing AVR had significantly larger LV end‐diastolic and end‐systolic volumes than their counterparts. After a median follow‐up of 46 months (interquartile range: 17 to 78 months), both groups of patients showed a significant and sustained reduction in LV end‐diastolic and end‐systolic volumes, with significantly larger reduction in patients undergoing AVR. Ejection fraction decreased significantly postoperatively and improved later during follow‐up similarly in both groups. The incidence of significant AR at long‐term follow‐up was comparable among groups (AVr: 8% vs. AVR: 7%). Conclusions LV reverse remodeling occurs after AVR and AVr, reaching comparable LV volumes and function after a median of four years of follow‐up. doi: 10.1111/jocs.12457 (J Card Surg 2015;30:13–19)